A kind of high gloss ceramic and preparation method thereof

Through the combined glaze application and medium-temperature sintering process of ceramic body and glaze, combined with the reinforcement agent adjusted by the modified liquid and the modified basalt fiber agent, the problem of insufficient performance of ceramic products is solved, and high gloss, strength and acid resistance are achieved Improved alkali stability.

CN119143471BActive Publication Date: 2025-02-18DEHUA COUNTY KAIDELI ARTS & CRAFTS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411603617.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing ceramic products have poor high gloss performance, poor bending strength, wear resistance and acid and alkali resistance, which limits the efficiency of the product.

Method used

The combined glaze application method of ceramic body and glaze is adopted to optimize the sintering uniformity through the medium-temperature sintering process, and the modified liquid-adjusted reinforcement and modified basalt fiber agent are added to the blank body and glaze to improve the performance of the product. .

Benefits of technology

It achieves high gloss, excellent flexural strength, wear resistance and significant acid and alkali resistance of ceramic products, and improves product usage efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramics, and in particular to a high-gloss ceramic and a preparation method thereof, comprising the following steps: 35-45 parts of kaolin, 20-25 parts of illite, 10-15 parts of dolomite, 8-12 parts of talc and 6-10 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture, and a glaze is applied to a ceramic body, and the glaze amount is 550 g / m 2 The high-gloss ceramics of the present invention are made of ceramic blanks, glazed with glaze materials and sintered at medium temperature. The obtained ceramic products have high gloss and excellent bending strength and wear resistance. At the same time, the acid and alkali resistance of the products are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a high-gloss ceramic and a preparation method thereof. Background Art

[0002] Daily-use ceramics refer to ceramics used for food, that is, ceramic products such as plates, bowls, cups, and saucers. The emergence of daily-use ceramics can be said to be due to people's needs in daily life. In daily life, people come into contact with the most and are the most familiar with porcelain, such as tableware, tea sets, coffee sets, wine sets, dining sets, etc.

[0003] Existing ceramic products have poor high gloss performance, poor bending strength and wear resistance, and poor acid and alkali stability, which limits the use efficiency of the products. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a high-gloss ceramic and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a method for preparing high-gloss ceramics, comprising the following steps:

[0007] Step 1: by weight, 35-45 parts of kaolin, 20-25 parts of illite, 10-15 parts of dolomite, 8-12 parts of talc and 6-10 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture;

[0008] Step 2: 10-15 parts by weight of a reinforcing agent adjusted by a modifying liquid, 5-8 parts of a modified basalt fiber agent and the mixture of step 1 are uniformly blended, and then the mixture is kneaded and formed to obtain a ceramic body;

[0009] Step 3: Preparation of glaze:

[0010] According to weight, 20-25 parts of albite, 10-15 parts of quartz, 8-12 parts of nano-alumina, 4-7 parts of nano-silicon dioxide, 1-3 parts of sodium carboxymethyl cellulose, 2-4 parts of stearic acid and 5-8 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze;

[0011] Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

[0012] Preferably, the specific operation steps of the medium temperature sintering treatment are:

[0013] First, sinter at 550~650℃ for 1~2h, then heat to 1220~1230℃ at a rate of 2~3℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 1~3℃ / min.

[0014] The mass fraction of the chitosan solution is 3-5%.

[0015] Preferably, the preparation method of the reinforcing agent based on modification liquid adjustment is:

[0016] S01: immersing wollastonite in a lanthanum chloride solution of 2 to 5 times the total mass of wollastonite, and then adding 5 to 8% of the total mass of wollastonite nano-titanium dioxide and 3 to 5% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution;

[0017] S02: treating the pyrophyllite in a plasma box for 10-15 minutes at a treatment power of 350-400W, and obtaining plasma-treated pyrophyllite after the treatment is completed;

[0018] S03: By weight, 3-5 parts of zirconium oxide, 1-3 parts of citric acid and 2-4 parts of sodium lignin sulfonate solution are mixed evenly to obtain a zirconium oxide tonic solution;

[0019] S04: According to weight, 5-7 parts of plasma-treated pyrophyllite and 3-4 parts of zirconium oxide tonic liquid are mixed and ball-milled at a speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a tonic agent;

[0020] S05: Stirring the reinforcing agent and the modifying liquid in a weight ratio of 2:(4-5) to obtain a reinforcing agent adjusted based on the modifying liquid.

[0021] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 2-4%.

[0022] Preferably, the stirring temperature of the stirring treatment in S05 is 50-55° C., the stirring speed is 550-600 r / min, and the stirring time is 30-40 min.

[0023] Preferably, the preparation method of the modified basalt fiber agent is:

[0024] S11: soaking the basalt fiber in a sufficient amount of potassium permanganate solution with a mass fraction of 5-8%, the soaking temperature is 48-52°C, the soaking time is 35-45 minutes, and after the soaking, the fiber is washed with water, filtered and dried;

[0025] S12: by weight, 2-4 parts of tetrabutyl titanate and 1-3 parts of silane coupling agent KH550 are added to 5-8 parts of 3-6% cobalt nitrate solution, and then 5-7 parts of basalt fiber of S101 are added and blended by ultrasonic to obtain basalt fiber agent;

[0026] S13: According to weight, 6-9 parts of basalt fiber agent and 5-8 parts of ball milling additive are mixed and ball milled. After the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent.

[0027] Preferably, the ultrasonic power of the blending ultrasound in S12 is 350-400 W, and the ultrasonic time is 20-30 min; the ball milling speed of the blending ball milling in S13 is 750-850 r / min, and the ball milling is 1 h.

[0028] Preferably, the ball milling additive comprises the following raw materials in parts by weight:

[0029] 3-5 parts by weight of silicon carbide, 2-3 parts by weight of nano-hydroxyapatite, 4-6 parts of cerium nitrate solution and 0.25-0.35 parts of calcined zinc oxide solution;

[0030] The preparation method of calcined zinc oxide liquid is as follows: calcine nano zinc oxide at 210-230° C. for 1 hour, then cool to room temperature, and then add into a sufficient amount of 5% by mass sodium silicate solution and mix thoroughly to obtain calcined zinc oxide liquid.

[0031] Preferably, the mass fraction of the cerium nitrate solution is 2-5%.

[0032] The present invention also provides a high-gloss ceramic, which is prepared by the high-gloss ceramic preparation method.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1. The high-gloss ceramics of the present invention are made of ceramic green bodies, glazed with glaze materials, and sintered at medium temperature. In the medium-temperature sintering, medium-temperature sintering is first adopted, and then the temperature is increased step by step, and then the temperature is reduced step by step to optimize the sintering uniformity. The obtained ceramic products have high gloss and excellent bending strength and wear resistance of the ceramic products. At the same time, the acid and alkali stability of the products are remarkable;

[0035] 2. In the preparation of ceramic green bodies, kaolin, illite, dolomite, talc and potassium feldspar are mixed and milled as the base material, and the reinforcing agent and modified basalt fiber agent adjusted by the modified liquid are added, and the two raw materials are used as fillers to further fill the matrix, improve the performance of the green body product, and optimize the product's flexural strength, wear resistance and acid and alkali resistance stability;

[0036] At the same time, the glaze is mixed with albite, quartz, nano-alumina, nano-silicon dioxide, sodium carboxymethyl cellulose, stearic acid and chitosan solution. Through the coordination of the raw materials, the prepared glaze is applied to the ceramic body, and the obtained ceramic product has excellent high gloss performance;

[0037] 3. The reinforcing agent based on the adjustment of the modified liquid adopts wollastonite in combination with lanthanum chloride solution, nano titanium dioxide and sodium dodecylbenzene sulfonate. Through the coordination and matching between the raw materials, lanthanum chloride solution is used as the matrix raw material, and sodium dodecylbenzene sulfonate is coordinated to enhance the interfacial activity of the modified liquid. At the same time, nano titanium dioxide and wollastonite are coordinated, and the needle-shaped wollastonite carries nano titanium dioxide, so that the obtained modified liquid can better reinforce the raw materials of the system in the system and improve the performance of the product. The pyrophyllite is treated in a plasma box to stimulate the active efficiency of the pyrophyllite, and then zirconium oxide, citric acid and sodium lignin sulfonate solution are uniformly blended to obtain zirconium oxide reinforcing liquid. The zirconium oxide reinforcing liquid is used to blend the pyrophyllite, and the reinforcing agent obtained is better coordinated with the modified liquid. The pyrophyllite in the reinforcing agent is better coordinated with zirconium oxide and other raw materials in the modified liquid, so that the reinforcing agent based on the adjustment of the modified liquid can better reinforce the performance of the product system.

[0038] 4. The basalt fiber in the modified basalt fiber agent is immersed in potassium permanganate solution to optimize the activity efficiency of the basalt fiber. At the same time, it is combined with tetrabutyl titanate, silane coupling agent KH550 and 3-6% cobalt nitrate solution. Through the coordination between the raw materials, the basalt fiber is used as the matrix to further fill the system structure and enhance the stability of the system structure. At the same time, it is improved by ball milling with ball milling additives. The silicon carbide, nano-hydroxyapatite, cerium nitrate solution and calcined zinc oxide liquid in the ball milling additives are blended and blended. The calcined zinc oxide liquid is treated with zinc oxide calcination and then improved with sodium silicate solution. The improved calcined zinc oxide liquid is better matched in the silicon carbide, nano-hydroxyapatite and cerium nitrate solution system. The raw materials in the ball milling additives are coordinated and blended together to further strengthen the system structure and further enhance the performance of the obtained product. DETAILED DESCRIPTION

[0039] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] A method for preparing a high-gloss ceramic in this embodiment includes the following steps:

[0041] Step 1: by weight, 35-45 parts of kaolin, 20-25 parts of illite, 10-15 parts of dolomite, 8-12 parts of talc and 6-10 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture;

[0042] Step 2: 10-15 parts by weight of a reinforcing agent adjusted by a modifying liquid, 5-8 parts of a modified basalt fiber agent and the mixture of step 1 are uniformly blended, and then the mixture is kneaded and formed to obtain a ceramic body;

[0043] Step 3: Preparation of glaze:

[0044] According to weight, 20-25 parts of albite, 10-15 parts of quartz, 8-12 parts of nano-alumina, 4-7 parts of nano-silicon dioxide, 1-3 parts of sodium carboxymethyl cellulose, 2-4 parts of stearic acid and 5-8 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze;

[0045] Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

[0046] The specific operation steps of the medium temperature sintering process in this embodiment are:

[0047] First, sinter at 550~650℃ for 1~2h, then heat to 1220~1230℃ at a rate of 2~3℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 1~3℃ / min.

[0048] The mass fraction of the chitosan solution is 3-5%.

[0049] The preparation method of the reinforcing agent based on the modification liquid adjustment of this embodiment is:

[0050] S01: immersing wollastonite in a lanthanum chloride solution of 2 to 5 times the total mass of wollastonite, and then adding 5 to 8% of the total mass of wollastonite nano-titanium dioxide and 3 to 5% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution;

[0051] S02: treating the pyrophyllite in a plasma box for 10-15 minutes at a treatment power of 350-400W, and obtaining plasma-treated pyrophyllite after the treatment is completed;

[0052] S03: By weight, 3-5 parts of zirconium oxide, 1-3 parts of citric acid and 2-4 parts of sodium lignin sulfonate solution are mixed evenly to obtain a zirconium oxide tonic solution;

[0053] S04: According to weight, 5-7 parts of plasma-treated pyrophyllite and 3-4 parts of zirconium oxide tonic liquid are mixed and ball-milled at a speed of 1000-1500 r / min for 2 hours. After the ball milling is completed, the mixture is filtered and dried to obtain a tonic agent;

[0054] S05: Stirring the reinforcing agent and the modifying liquid in a weight ratio of 2:(4-5) to obtain a reinforcing agent adjusted based on the modifying liquid.

[0055] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 2-4%.

[0056] The stirring temperature of the stirring treatment in S05 of this embodiment is 50-55° C., the stirring speed is 550-600 r / min, and the stirring time is 30-40 min.

[0057] The preparation method of the modified basalt fiber agent of this embodiment is:

[0058] S11: soaking the basalt fiber in a sufficient amount of potassium permanganate solution with a mass fraction of 5-8%, the soaking temperature is 48-52°C, the soaking time is 35-45 minutes, and after the soaking, the fiber is washed with water, filtered and dried;

[0059] S12: by weight, 2-4 parts of tetrabutyl titanate and 1-3 parts of silane coupling agent KH550 are added to 5-8 parts of 3-6% cobalt nitrate solution, and then 5-7 parts of basalt fiber of S101 are added and blended by ultrasonic to obtain basalt fiber agent;

[0060] S13: According to weight, 6-9 parts of basalt fiber agent and 5-8 parts of ball milling additive are mixed and ball milled. After the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent.

[0061] The ultrasonic power of the blending in S12 of this embodiment is 350-400 W, and the ultrasonic time is 20-30 min. The ball milling speed of the blending in S13 is 750-850 r / min, and the ball milling is performed for 1 h.

[0062] The ball milling additive of this embodiment includes the following raw materials in parts by weight:

[0063] 3-5 parts by weight of silicon carbide, 2-3 parts by weight of nano-hydroxyapatite, 4-6 parts of cerium nitrate solution and 0.25-0.35 parts of calcined zinc oxide solution;

[0064] The preparation method of calcined zinc oxide liquid is as follows: calcine nano zinc oxide at 210-230° C. for 1 hour, then cool to room temperature, and then add into a sufficient amount of 5% by mass sodium silicate solution and mix thoroughly to obtain calcined zinc oxide liquid.

[0065] The mass fraction of the cerium nitrate solution in this embodiment is 2-5%.

[0066] The high-gloss ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss ceramic.

[0067] Embodiment 1: A method for preparing high-gloss ceramics, comprising the following steps:

[0068] Step 1: According to weight, 35 parts of kaolin, 20 parts of illite, 10 parts of dolomite, 8 parts of talc and 6 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture;

[0069] Step 2: 10 parts by weight of a reinforcing agent adjusted by a modifying liquid, 5 parts of a modified basalt fiber agent and the mixture of step 1 are uniformly blended, and then the mixture is kneaded and formed to obtain a ceramic body;

[0070] Step 3: Preparation of glaze:

[0071] According to weight, 20 parts of albite, 10 parts of quartz, 8 parts of nano-alumina, 4 parts of nano-silicon dioxide, 1 part of sodium carboxymethyl cellulose, 2 parts of stearic acid and 5 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze;

[0072] Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

[0073] The specific operation steps of the medium temperature sintering process in this embodiment are:

[0074] First, sinter at 550℃ for 1h, then heat to 1220℃ at a rate of 2℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 1℃ / min.

[0075] The mass fraction of the chitosan solution is 3%.

[0076] The preparation method of the reinforcing agent based on the modification liquid adjustment of this embodiment is:

[0077] S01: immersing wollastonite in a lanthanum chloride solution twice the total mass of wollastonite, and then adding 5% of the total mass of wollastonite nano-titanium dioxide and 3% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution;

[0078] S02: treating the pyrophyllite in a plasma box for 10 minutes at a treatment power of 350 W, and then completing the treatment to obtain plasma-treated pyrophyllite;

[0079] S03: 3 parts of zirconium oxide, 1 part of citric acid and 2 parts of sodium lignin sulfonate solution are mixed evenly by weight to obtain a zirconium oxide tonic solution;

[0080] S04: According to weight, 5 parts of plasma-treated pyrophyllite and 3 parts of zirconium oxide tonic liquid are mixed and ball-milled at a ball-milling speed of 1000 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a tonic agent;

[0081] S05: The reinforcing agent and the modifying liquid are stirred at a weight ratio of 2:4 to obtain a reinforcing agent adjusted based on the modifying liquid.

[0082] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the sodium lignin sulfonate solution is 2%.

[0083] The stirring temperature of the stirring treatment in S05 of this embodiment is 50° C., the stirring speed is 550 r / min, and the stirring time is 30 min.

[0084] The preparation method of the modified basalt fiber agent of this embodiment is:

[0085] S11: soaking the basalt fiber in a sufficient amount of 5% by mass potassium permanganate solution at a temperature of 48° C. for 35 minutes, washing, filtering and drying after the soaking is completed;

[0086] S12: by weight, 2 parts of tetrabutyl titanate and 1 part of silane coupling agent KH550 were added to 5 parts of 3% cobalt nitrate solution, and then 5 parts of basalt fiber of S101 were added and blended by ultrasonic to obtain basalt fiber agent;

[0087] S13: According to weight, 6 parts of basalt fiber agent and 5 parts of ball milling additive are mixed and ball milled. After the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent.

[0088] The ultrasonic power of the blending in S12 of this embodiment is 350 W, and the ultrasonic time is 20 min. The ball milling speed of the blending in S13 is 750 r / min, and the ball milling is performed for 1 h.

[0089] The ball milling additive of this embodiment includes the following raw materials in parts by weight:

[0090] 3 parts by weight of silicon carbide, 2 parts by weight of nano-hydroxyapatite, 4 parts of cerium nitrate solution and 0.25 parts of calcined zinc oxide solution;

[0091] The preparation method of calcined zinc oxide liquid is as follows: calcine nano zinc oxide at 210° C. for 1 hour, then cool to room temperature, and then add into a sufficient amount of 5% by mass sodium silicate solution and mix thoroughly to obtain calcined zinc oxide liquid.

[0092] The mass fraction of the cerium nitrate solution in this embodiment is 2%.

[0093] The high-gloss ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss ceramic.

[0094] Embodiment 2: A method for preparing high-gloss ceramics, comprising the following steps:

[0095] Step 1: According to weight, 45 parts of kaolin, 25 parts of illite, 15 parts of dolomite, 12 parts of talc and 10 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture;

[0096] Step 2: 15 parts of reinforcing agent adjusted by modifying liquid, 8 parts of modified basalt fiber agent and the mixture of step 1 are uniformly blended by weight, and then the mixture is kneaded and formed to obtain a ceramic body;

[0097] Step 3: Preparation of glaze:

[0098] According to weight, 25 parts of albite, 15 parts of quartz, 12 parts of nano-alumina, 7 parts of nano-silicon dioxide, 3 parts of sodium carboxymethyl cellulose, 4 parts of stearic acid and 8 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze;

[0099] Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

[0100] The specific operation steps of the medium temperature sintering process in this embodiment are:

[0101] First, sinter at 650℃ for 2h, then heat to 1230℃ at a rate of 3℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 3℃ / min.

[0102] The mass fraction of the chitosan solution is 5%.

[0103] The preparation method of the reinforcing agent based on the modification liquid adjustment of this embodiment is:

[0104] S01: immersing wollastonite in a lanthanum chloride solution of 5 times the total mass of wollastonite, and then adding 8% of the total mass of wollastonite nano-titanium dioxide and 5% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution;

[0105] S02: treating the pyrophyllite in a plasma box for 15 minutes at a treatment power of 400 W, and then completing the treatment to obtain plasma-treated pyrophyllite;

[0106] S03: 5 parts of zirconium oxide, 3 parts of citric acid and 4 parts of sodium lignin sulfonate solution are mixed evenly by weight to obtain a zirconium oxide tonic solution;

[0107] S04: According to weight, 7 parts of plasma-treated pyrophyllite and 4 parts of zirconium oxide tonic liquid were mixed and ball-milled at a speed of 1500 r / min for 2 h. After the ball milling was completed, the mixture was filtered and dried to obtain a tonic agent;

[0108] S05: The reinforcing agent and the modifying liquid are stirred at a weight ratio of 2:5 to obtain a reinforcing agent adjusted based on the modifying liquid.

[0109] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the sodium lignin sulfonate solution is 4%.

[0110] The stirring temperature of the stirring treatment in S05 of this embodiment is 55° C., the stirring speed is 600 r / min, and the stirring time is 40 min.

[0111] The preparation method of the modified basalt fiber agent of this embodiment is:

[0112] S11: soaking the basalt fiber in a sufficient amount of potassium permanganate solution with a mass fraction of 8%, the soaking temperature is 52°C, the soaking time is 45 minutes, and after the soaking is completed, the fiber is washed with water, filtered, and dried;

[0113] S12: by weight, 4 parts of tetrabutyl titanate and 3 parts of silane coupling agent KH550 were added to 8 parts of 6% cobalt nitrate solution, and then 7 parts of basalt fiber of S101 were added and blended by ultrasonic to obtain basalt fiber agent;

[0114] S13: According to weight, 9 parts of basalt fiber agent and 8 parts of ball milling additive are mixed and ball milled. After the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent.

[0115] The ultrasonic power of the blending in S12 of this embodiment is 400 W, and the ultrasonic time is 30 min. The ball milling speed of the blending in S13 is 850 r / min, and the ball milling is performed for 1 h.

[0116] The ball milling additive of this embodiment includes the following raw materials in parts by weight:

[0117] 5 parts by weight of silicon carbide, 3 parts by weight of nano-hydroxyapatite, 6 parts of cerium nitrate solution and 0.35 parts of calcined zinc oxide solution;

[0118] The preparation method of calcined zinc oxide liquid is as follows: calcine nano zinc oxide at 230° C. for 1 hour, then cool to room temperature, and then add into a sufficient amount of 5% by mass sodium silicate solution and mix thoroughly to obtain calcined zinc oxide liquid.

[0119] The mass fraction of the cerium nitrate solution in this embodiment is 5%.

[0120] The high-gloss ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss ceramic.

[0121] Embodiment 3: A method for preparing high-gloss ceramics, comprising the following steps:

[0122] Step 1: According to weight, 40 parts of kaolin, 22.5 parts of illite, 12.5 parts of dolomite, 10 parts of talc and 8 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture;

[0123] Step 2: 12.5 parts of reinforcing agent adjusted by modifying liquid, 6.5 parts of modified basalt fiber agent and the mixture of step 1 are uniformly blended by weight, and then kneaded and formed to obtain a ceramic body;

[0124] Step 3: Preparation of glaze:

[0125] According to weight, 22.5 parts of albite, 12.5 parts of quartz, 10 parts of nano-alumina, 5.5 parts of nano-silicon dioxide, 2 parts of sodium carboxymethyl cellulose, 3 parts of stearic acid and 6.5 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze;

[0126] Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

[0127] The specific operation steps of the medium temperature sintering process in this embodiment are:

[0128] First, sinter at 600℃ for 1.5h, then heat to 1225℃ at a rate of 2.5℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 2℃ / min.

[0129] The mass fraction of the chitosan solution is 4%.

[0130] The preparation method of the reinforcing agent based on the modification liquid adjustment of this embodiment is:

[0131] S01: immersing wollastonite in a lanthanum chloride solution of 3.5 times the total mass of wollastonite, and then adding 6.5% of the total mass of wollastonite nano-titanium dioxide and 4% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution;

[0132] S02: treating the pyrophyllite in a plasma box for 12.5 min at a treatment power of 370 W, and completing the treatment to obtain plasma-treated pyrophyllite;

[0133] S03: 4 parts of zirconium oxide, 2 parts of citric acid and 3 parts of sodium lignin sulfonate solution are mixed evenly by weight to obtain a zirconium oxide tonic solution;

[0134] S04: According to weight, 6 parts of plasma-treated pyrophyllite and 3.5 parts of zirconium oxide tonic liquid were mixed and ball-milled at a speed of 1250 r / min for 2 h. After the ball milling was completed, the mixture was filtered and dried to obtain a tonic agent;

[0135] S05: The reinforcing agent and the modifying liquid are stirred at a weight ratio of 2:4.5 to obtain a reinforcing agent adjusted based on the modifying liquid.

[0136] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the sodium lignin sulfonate solution is 3%.

[0137] The stirring temperature of the stirring treatment in S05 of this embodiment is 52.5° C., the stirring speed is 570 r / min, and the stirring time is 35 min.

[0138] The preparation method of the modified basalt fiber agent of this embodiment is:

[0139] S11: soaking the basalt fiber in a sufficient amount of potassium permanganate solution with a mass fraction of 6.5%, the soaking temperature is 50° C., the soaking time is 40 min, and after the soaking is completed, the basalt fiber is washed with water, filtered, and dried;

[0140] S12: by weight, 3 parts of tetrabutyl titanate and 2 parts of silane coupling agent KH550 were added to 6.5 parts of 4.5% cobalt nitrate solution, and then 6 parts of basalt fiber of S101 were added and blended by ultrasonic to obtain basalt fiber agent;

[0141] S13: According to weight, 7.5 parts of basalt fiber agent and 6.5 parts of ball milling additive are mixed and ball milled. After the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent.

[0142] The ultrasonic power of the blending ultrasound in S12 of this embodiment is 370W, and the ultrasonic time is 25min; the ball milling speed of the blending ball milling in S13 is 800r / min, and the ball milling is 1h.

[0143] The ball milling additive of this embodiment includes the following raw materials in parts by weight:

[0144] 4 parts by weight of silicon carbide, 2.5 parts by weight of nano-hydroxyapatite, 5 parts of cerium nitrate solution and 0.30 parts of calcined zinc oxide solution;

[0145] The preparation method of calcined zinc oxide liquid is as follows: calcine nano zinc oxide at 220° C. for 1 hour, then cool to room temperature, and then add into a sufficient amount of 5% by mass sodium silicate solution and mix thoroughly to obtain calcined zinc oxide liquid.

[0146] The mass fraction of the cerium nitrate solution in this embodiment is 3.5%.

[0147] The high-gloss ceramic of this embodiment is prepared by the above-mentioned preparation method of the high-gloss ceramic.

[0148] Comparative Example 1:

[0149] The difference from Example 3 is that no reinforcing agent adjusted by the modifying liquid is added.

[0150] Comparative Example 2:

[0151] The difference from Example 3 is that no strengthening agent is added in the preparation of the strengthening agent based on the adjustment of the modifying liquid.

[0152] Comparative Example 3:

[0153] The difference from Example 3 is that no plasma-treated pyrophyllite is added to the tonic enhancer.

[0154] Comparative Example 4:

[0155] The difference from Example 3 is that no zirconium oxide tonic liquid is added to the tonic enhancer.

[0156] Comparative Example 5:

[0157] The difference from Example 3 is that no modifying liquid is added in the preparation of the reinforcing agent based on the adjustment of the modifying liquid.

[0158] Comparative Example 6:

[0159] The difference from Example 3 is that the preparation method of the modified liquid is different;

[0160] The nano-titanium dioxide is first immersed in a 5% sodium dodecylbenzene sulfonate solution which is 3.5 times the total mass of the nano-titanium dioxide and then fully mixed to obtain a modified solution.

[0161] Comparative Example 7:

[0162] The difference from Example 3 is that no modified basalt fiber agent is added.

[0163] Comparative Example 8:

[0164] The difference from Example 3 is that no basalt fiber agent is added in the preparation of the modified basalt fiber agent.

[0165] Comparative Example 9:

[0166] The difference from Example 3 is that no basalt fiber of S101 is added in the preparation of the basalt fiber agent.

[0167] Comparative Example 10:

[0168] The difference from Example 3 is that tetrabutyl titanate is not added in the preparation of the basalt fiber agent, and the cobalt nitrate solution is replaced by water.

[0169] Comparative Example 11:

[0170] The difference from Example 3 is that no ball milling additive is added in the preparation of the modified basalt fiber agent.

[0171] The products of Examples 1 to 3 and Comparative Examples 1 to 11 were subjected to conventional performance tests, and were placed at 70°C for 12 hours, then placed under 5% hydrochloric acid mist conditions for 24 hours, and then placed under 5% sodium hydroxide alkaline mist conditions for 24 hours. The above was one cycle, and the test was repeated 5 times to test the acid and alkali stability of the products. The test results are shown in Table 1.

[0172] Table 1 Product performance test results of Examples 1 to 3 and Comparative Examples 1 to 11:

[0173]

[0174] It can be seen from Comparative Examples 1-11 and Examples 1-3 that the product of Example 3 has excellent bending strength, and also excellent wear resistance and glossiness performance, and the three can be improved in a coordinated manner. In addition, the product has excellent stability performance under acid and alkali resistance conditions;

[0175] The present invention does not add a reinforcing agent based on the modification liquid adjustment and does not add a modified basalt fiber agent, and the performance of the product deteriorates significantly, and the performance stability of the product deteriorates significantly under acid and alkali resistance conditions; the two are used in combination, and the synergistic effect of the product is the most significant;

[0176] The performance of the products tended to deteriorate to varying degrees when no reinforcing agent was added to the reinforcing agent prepared based on the modification liquid, no plasma-treated pyrophyllite was added to the reinforcing agent, no zirconium oxide reinforcing liquid was added to the reinforcing agent, no modifying liquid was added to the reinforcing agent prepared based on the modification liquid, and the preparation methods of the modifying liquid were different;

[0177] The reinforcing agent prepared by the specific method of the present invention and the modifying liquid obtained by the method of the present invention is the most significant product. Other methods are not as significant as the present invention.

[0178] The performance of the products without adding basalt fiber agent, without adding S101 basalt fiber, without adding tetrabutyl titanate, replacing cobalt nitrate solution with water, and without adding ball milling additives in the preparation of modified basalt fiber agent all showed different degrees of deterioration trend. The performance deterioration trend was the greatest in the preparation of modified basalt fiber agent without adding ball milling additives.

[0179] The basalt fiber agent obtained by the specific method of the present invention is combined with a ball milling additive, and the product performance effect is the most significant. Other methods are not as obvious as the effect of the present invention.

[0180] The present invention further explores the product performance through the composition of ball milling additives.

[0181] Experimental Example 1:

[0182] The only difference from Example 3 is that silicon carbide is not added to the ball milling additive.

[0183] Experimental Example 2:

[0184] The only difference from Example 3 is that no nano-hydroxyapatite is added to the ball milling additive.

[0185] Experimental Example 3:

[0186] The only difference from Example 3 is that no calcined zinc oxide solution is added to the ball milling additive.

[0187] Experimental Example 4:

[0188] The only difference from Example 3 is that the calcined zinc oxide solution is directly replaced by nano zinc oxide.

[0189] Experimental Example 5:

[0190] The only difference from Example 3 is that the cerium nitrate solution is replaced by water.

[0191] The products of Experimental Examples 1 to 5 were subjected to conventional performance tests, and were placed at 70°C for 12 hours, then placed under 5% hydrochloric acid mist conditions for 24 hours, and placed under 5% sodium hydroxide alkaline mist conditions for 24 hours. The above was one cycle, and the test was repeated 5 times to test the acid and alkali stability of the products. The test results are shown in Table 2.

[0192] Table 2 Product performance test results of Experimental Examples 1 to 5:

[0193]

[0194] It can be seen from Experimental Examples 1-5 that calcined zinc oxide liquid and silicon carbide are not added to the ball milling additive, and the performance of the product changes. Among the components of the ball milling additive, the conventional performance and acid and alkali resistance stability deteriorate most significantly, followed by the fact that nano-hydroxyapatite is not added to the ball milling additive, the calcined zinc oxide liquid is directly replaced by nano-zinc oxide, and the cerium nitrate solution is replaced by water. The performance of the product has a tendency to deteriorate. The raw materials of the ball milling additive composition change, and the performance of the product has a tendency to deteriorate. The use of other methods to replace the composition of the ball milling additive is not as significant as the effect of the present invention. The composition of the ball milling additive of the present invention is unique.

[0195] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0196] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing high-gloss ceramics, characterized in that: The following steps are involved: Step 1: by weight, 35-45 parts of kaolin, 20-25 parts of illite, 10-15 parts of dolomite, 8-12 parts of talc and 6-10 parts of potassium feldspar are blended and ball-milled, and the mixture is passed through a 250-mesh sieve to obtain a mixture; Step 2: 10-15 parts by weight of a reinforcing agent adjusted by a modifying liquid, 5-8 parts of a modified basalt fiber agent and the mixture of step 1 are uniformly blended, and then the mixture is kneaded and formed to obtain a ceramic body; The preparation method of the reinforcing agent based on modification liquid adjustment is: S01: immersing wollastonite in a lanthanum chloride solution of 2 to 5 times the total mass of wollastonite, and then adding 5 to 8% of the total mass of wollastonite nano-titanium dioxide and 3 to 5% of the total mass of wollastonite sodium dodecylbenzene sulfonate to fully mix to obtain a modified solution; S02: treating the pyrophyllite in a plasma box for 10-15 minutes at a treatment power of 350-400W, and obtaining plasma-treated pyrophyllite after the treatment is completed; S03: By weight, 3-5 parts of zirconium oxide, 1-3 parts of citric acid and 2-4 parts of sodium lignin sulfonate solution are uniformly mixed to obtain a zirconium oxide tonic solution; S04: According to weight, 5-7 parts of plasma-treated pyrophyllite and 3-4 parts of zirconium oxide tonic liquid are mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours. After the ball-milling is completed, the mixture is filtered and dried to obtain a tonic agent; S05: stirring the reinforcing agent and the modifying liquid in a weight ratio of 2:(4-5) to obtain a reinforcing agent adjusted by the modifying liquid; The preparation method of the modified basalt fiber agent is: S11: soaking the basalt fiber in a sufficient amount of potassium permanganate solution with a mass fraction of 5-8%, the soaking temperature is 48-52°C, the soaking time is 35-45 minutes, and after the soaking, the fiber is washed, filtered and dried; S12: by weight, 2-4 parts of tetrabutyl titanate and 1-3 parts of silane coupling agent KH550 are added to 5-8 parts of 3-6% by mass cobalt nitrate solution, and then 5-7 parts of basalt fiber treated by S11 are added and blended by ultrasonic to obtain a basalt fiber agent; S13: by weight, 6-9 parts of basalt fiber agent and 5-8 parts of ball milling additive are mixed and ball milled, and after the ball milling is completed, the mixture is filtered and dried to obtain a modified basalt fiber agent; The ball milling additive comprises the following raw materials in parts by weight: 3-5 parts by weight of silicon carbide, 2-3 parts by weight of nano-hydroxyapatite, 4-6 parts of cerium nitrate solution and 0.25-0.35 parts of calcined zinc oxide solution; The preparation method of the calcined zinc oxide liquid is as follows: calcining the nano zinc oxide at 210-230° C. for 1 hour, cooling to room temperature, and then adding to a sufficient amount of 5% by mass sodium silicate solution and mixing well to obtain the calcined zinc oxide liquid; Step 3: Preparation of glaze: According to weight, 20-25 parts of albite, 10-15 parts of quartz, 8-12 parts of nano-alumina, 4-7 parts of nano-silicon dioxide, 1-3 parts of sodium carboxymethyl cellulose, 2-4 parts of stearic acid and 5-8 parts of chitosan solution are mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a glaze; Step 4: Apply glaze to the ceramic body with a glaze amount of 550g / m 2 , and then sintered at medium temperature. After sintering, high-gloss ceramics are obtained.

2. The method for preparing high-gloss ceramics according to claim 1, characterized in that: The specific operation steps of the medium temperature sintering treatment are: First, sinter at 550~650℃ for 1~2h, then heat to 1220~1230℃ at a rate of 2~3℃ / min, sinter for 2h, and finally cool to room temperature at a rate of 1~3℃ / min. The mass fraction of the chitosan solution is 3-5%.

3. The method for preparing high-gloss ceramics according to claim 1, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the sodium lignin sulfonate solution is 2-4%.

4. The method for preparing high gloss ceramics according to claim 1, characterized in that: The stirring temperature of the stirring treatment in S05 is 50-55° C., the stirring speed is 550-600 r / min, and the stirring time is 30-40 min.

5. The method for preparing high gloss ceramics according to claim 1, characterized in that: The ultrasonic power of the blending in S12 is 350-400 W, and the ultrasonic time is 20-30 min. The ball milling speed of the blending in S13 is 750-850 r / min, and the ball milling is performed for 1 h.

6. The method for preparing high gloss ceramics according to claim 1, characterized in that: The mass fraction of the cerium nitrate solution is 2-5%.

7. A high-gloss ceramic prepared by the preparation method of the high-gloss ceramic according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Production process of graphene-containing ceramic

    CN111848121A